A Study on Consumer Buying behavior towards online shopping at Marwar Region (Rajasthan) - Khanna, Gaurav; Khanna, Gaurav; Bhandari, Deepak (International Journal of Psychosocial Rehabilitation, 2020)
This article analyse consumer buying for onlineshopping. In this study we would like to find the characteristics of the purchasing behavior of consumers shopping online. According to discussion on buying behavior of consumers regarding shopping onlinewas studied via internet using different socio- economic variables. Thiswill certainlyassist all consumer based  researchers toidentify with the driving factors behind purchaseapproach of consumers and objective to buy on the web browser andobservations of consumers concerningeasinessof exercise andworth fullness. An online display shows the physical resemblanceof buying products plus services from an internet superstore and this process of purchasing is called B2C onlineshopping.